WeMPiC protocol to prevent Deep Venous Thrombosis in patients with neurosurgical diseases - Thapa, Amit; KC, Bidur; Shakya, Bikram; Chakradhar, Rupesh (Nepal Journal of Neuroscience, 2020)
Background: Deep Venous Thrombosis is a common yet difficult problem to prevent in neurosurgical patients. Recent trials did not find sufficient evidence to support use of graduated compression stockings, however we believe, this inefficiency may be due to the method of application which needs to be modified. We have been following a patient specific mechanical prophylaxis protocol, nicknamed WeMPiC. This study aims to evaluate the effectiveness of WeMPiC protocol.Methods: An observational cohort study was performed including consecutive patients admitted to neurosurgical ICU who were bedridden for >7 days between April 2014 and September 2017. We developed WeMPiC protocol of early weaning off, early mobilization, limb physiotherapy and alternate two hours on and off application of thigh length graduated compression stockings. Lower limbs compression ultrasound studies were performed on alternate days.Results: One hundred thirty-one patients were included in the study. Mean age of patients was 53.7+ 20.6 years. Of these patients, 52.7% had stroke (91% had hemorrhages), 32.1% had head injury and 7.6% each had spine problem and brain tumor each. five (3.8%) developed deep venous thrombosis on the 4th and 6th day of ICU stay, mainly in popliteal veins (2.3%) and femoral veins (1.5%). Deep venous thrombosis was associated with younger age (47 years, p=0.005), ICU stay (13 days, p=0.014), Wells’ score (4.6, p